Examining the social component of sustainable forest management in Prince Albert and Vilhelmina Model Forests - Carlsson, Julia (2012)
Due to the forest industry downsizing, many communities in rural forest regions in Canada and Sweden are facing problems to survive. In order to create community sustainability, resilience and well-being in remote forest regions, the view on the forest resources has shifted towards multiple use, through the concept of sustainable forest management (SFM). Beside the economic and ecological elements of sustainability, the social forest values are needed, contributing to the human well-being, local participation, stakeholder collaboration, human rights and cultural connection. In this thesis the embodiment of the social component of SFM within Prince Albert Model Forest (Canada), and Vilhelmina Model Forest (Sweden) will be examined. Being partners and facing similar challenges as rural boreal forest regions, the two model forests are compared through analysis of projects and activities, conducted interviews and organization documents. Looking at projects mentioned as successful by the interviewees, they all have elements from the social values of SFM. The direction can be explained by the introduction of the Forest Communities Program in Canada, demanding the Model Forests to work towards community stability and resilience, the Model Forest organization concept itself and the way global focus are increasing around social forest values. In the future, it may be important that the role of the MFs enable some kind of political authorization and legitimacy in order to improve conflict solving and indigenous rights equality. Funding is crucial to run a Model Forest organization, enabling coordination and administration staff, representative participation and travel possibilities to meetings.